Study on treatment of hepatolithiasis using cholangioscopy through percutaneous trans-choledochojejunal anastomotic channel guided by ultrasound - KONG Xiangyu, LIANG Ting, ZHANG Cheng, HU Hai, TIAN Fuzhou, XIANG Yukai, Zhang Honglei, LÜ Beining, YANG Yulong (Waike lilun yu shijian, 2022)
Objective To investigate the procedure and efficacy in treatment of hepatolithiasis by percutaneous cholangioscopy through choledochojejunal anastomotic channel guided by ultrasound. Methods From June 2021 to January 2022, 6 patients with hepatolithiasis combined with stenosis of both intrahepatic duct and anastomosis after surgery with choledochojejunostomy were included in this study. The treatment including the removal of hepatolithiasis and dilation of intrahepatic duct and anastomotic stoma was performed by soft fiber-optic cholangioscopy through percutaneous trans-choledochojejunal anastomotic channel under ultrasound guidance. Results There were different procedures of channel establishment through percutaneous trans- choledochojejunal anastomosis for 6 cases. The ultrasound-guided percutaneous trans-choledochojejunal anastomotic channel was set up in 3 patients. There were 2 cases with cholangioscopy through percutaneous transhepatic cholangial drainage channel under ultrasound guidance. The other case after fail of percutaneous cholangioscopy was converted to laparotomy which showed choledochojejunal anastomosis located in the back of colon and the establishment of percutaneous trans-choledochojejunal anastomotic channel was done then. The cholangioscopy could reach the left or the right intrahepatic bile duct convenient through the channels for all 6 cases. There were no abdominal bleeding and infection, intestinal fistula, biliary leakage and other short-term complications postoperatively. During 1 to 6 months of follow up, the channels could be passed repeatedly for the procedures for stone removal, and dilation of intrahepatic duct stenosis and anastomotic stenosis. Conclusions The main advantages of percutaneous trans-choledochojejunal anastomotic channel under ultrasound guidance would be minimally invasive, safe, and effective for treatment of hepatolithiasis, intrahepatic duct stenosis and anastomotic stenosis.